PENGARUH TERAPI RELAKSASI AUTOGENIK TERHADAP PENURUNAN TINGKAT NYERI AKUT PADA PASIEN ABDOMINAL PAIN DI KABUPATEN BONE BOLANGO - Fitriyani Djunaid; Jumriana; Suryawijaya Sukma (Universitas Sam Ratulangi, 2023)
Background: Abdominal pain is the main symptom of an acute abdomen that occurs suddenly and not specific. Pain is an unpleasant sensory experience, the main element that must be present to be called pain is unpleasant feeling. Previous studies reported that autogenic relaxation therapy effectively reduces pain in patients with abdominal pain. Aim: This study aimed to analyze the effect of autogenic relaxation therapy on reducing acute pain levels in abdominal pain patients at Toto Kabila Hospital, District Bone Bolango. Methods: The research design used in this study was a pre-experimental design with one group pretest posttest design without comparison group (control). The number of samples was 10 respondents of abdominal pain. The type of intervention used is autogenic relaxation therapy with an evaluation of pain intensity. Results: The results of this study found that autogenic relaxation therapy had an effect on reducing the level of acute pain in abdominal pain patients with a p value of 0.003 < α 0.05. Conclusion: Relaxation therapy is effective in reducing pain response, these studies were conducted on acute and chronic pain. Keywords: Abdominal Pain; Painful; Autogenic Relaxation Therapy